MODELLING OF EXTENSIONAL FLOW BEHAVIOR OF POLYMERIC FLUID USING CAPILLARY THINNING EXPERIMENT - S. I. KAMAR; H.A. ADAMU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The study presents the stretching behavior exhibits by the viscoelastic fluid with the scope of investigating how the stretching flow method can be predicted from simple mathematical models of polymeric fluids. However, the stretching flow technique is used to determine the extensional properties of polymer liquids. Our results show that the stretching behavior of the polymeric fluid causes a decline in radius. Moreover, we observed that the exponential decay curve plays a significant contribution in determining the relaxation times. This was deduced from the governing equations of the radially squeezed cylindrical fluid column with the use of distinct non-dimensional parameters obtained from the force balance and three relaxation times were achieved. The curve appears to be Newtonian at the initial stage and then changed to elastic and cut-off in the final stage. The motive for this study is to provide a significant understanding of fluid flow phenomenon of polymeric liquid by stretching techniques and computations. This flow phenomenon was investigated with the view of understanding the rheological viewpoint governing the stretching behavior in elastic fluids and the techniques employed in determining these flow responses to deformation.